Issues and challenges in management of waqf in Ningxia Province of China - Binghai, Ma; Kassim, Salina (IIUM Press, 2017)
Waqf institutions in China are facing several issues and challenges such as waste of charitable resources, difficulties in retaining waqf assets, and low levels of professionalism of those involved in waqf. The internal management mechanisms of these institutions continue to be designed and controlled to support personal ambitions and control as opposed to the more religious considerations advocated by Islam and that align with the purpose of waqf. Despite this formidable challenge that permeates waqf in China, there has been a lack of research on these issues. This paper aims to fill this lacuna in the literature by investigating and assessing the management mechanism and national governance of both general and Islamic aspects of waqf in China. The paper adopts a qualitative method using semi-structured interviews with several senior waqf managers. The findings highlight several issues and challenges facing waqf in China, including the lack of a defined aim, low level of capability and professionalism, narrow-mindedness, and poor levels of coordination. Other issues include brain drain, unstable performance, low qualification, and managerial neglect of waqf managers. Lastly, the findings elaborate the balance point between China’s national governance and Islamic governance.